2015
DOI: 10.7554/elife.07789
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of Plasmodium sporozoite motility in the dermis reveals component of blood vessel recognition

Abstract: Malaria infection starts with injection of Plasmodium sporozoites by an Anopheles mosquito into the skin of the mammalian host. How sporozoites locate and enter a blood vessel is a critical, but poorly understood process. In this study, we examine sporozoite motility and their interaction with dermal blood vessels, using intravital microscopy in mice. Our data suggest that sporozoites exhibit two types of motility: in regions far from blood vessels, they exhibit ‘avascular motility’, defined by high speed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
161
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(176 citation statements)
references
References 28 publications
14
161
0
1
Order By: Relevance
“…[21] Intriguingly, we also found that sporozoites decrease their speed when circling around thinner pillars compared to larger pillars or when gliding in the absence of pillars ( Figure 5B). This could hint towards the existence of a mechanism that slows sporozoites down when they attach to an object with matching curvature, possibly by allowing the formation of adhesion sites on the surface of the object (a pillar in vitro and a blood vessel in vivo).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…[21] Intriguingly, we also found that sporozoites decrease their speed when circling around thinner pillars compared to larger pillars or when gliding in the absence of pillars ( Figure 5B). This could hint towards the existence of a mechanism that slows sporozoites down when they attach to an object with matching curvature, possibly by allowing the formation of adhesion sites on the surface of the object (a pillar in vitro and a blood vessel in vivo).…”
Section: Discussionmentioning
confidence: 65%
“…[19,20] In vivo experiments analyzing the tracks of many parasites further showed that sporozoites migrate with slightly reduced speed around capillaries compared to their migration in the surrounding tissue. [21] Around blood capillaries they also adapt a more uniform curvature that appears different from the surrounding tissue, where they often change their shape. [21] These observations led us to the hypothesis that sporozoites develop their curvature to select blood vessels of a matching curvature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant sporozoites with decreased migratory behavior and motility speed show dramatic reductions in invasion and infectivity, indicating that migration from the inoculation site poses a significant barrier and thus an ideal opportunity for intervention (Hopp et al 2015). Available data indicate that fewer than 100 sporozoites result in hepatocytic infection following the bite of a mosquito (Fig.…”
Section: Approaches To Development Of Vimtmentioning
confidence: 99%
“…Studies show that sporozoites recognize CD31+ blood vessels (Hopp et al, 2015) in their attempt to exit the dermis, suggesting the possibility of developing antibodies targeting this receptor that may inhibit sporozoites exit from the dermis.…”
Section: Recent Discoveries In Molecular Targets and Opportunities Avmentioning
confidence: 99%